Toma de decisiones en la apropiación de herramientas tecnológicas: una perspectiva de riesgo - Torres-Carballo, Federico (Instituto Tecnológico de Costa Rica, 2011)
This research aims to validate the proposed application of experimental techniques for the study of decision making in contexts learning situations. Articulates four economic experiments in a factorial design based on an instrument widely used in the literature of the field (Eckel & Grossman, 2007) to determine the risk aversion of students in business administration in the usual context of the experiment and in the context of face decision making about learning technology tools. In the latter case, the student develops a specific task in Microsoft Excel 2003 or Microsoft Excel 2007 to your preference and assumes no risk or try their hand at the new tool. For statistical modeling a set of conditional logistic regressions were performed to predict a binary outcome that expresses an aversion to risk. It was concluded from experiments that participants subject the instrument Eckel & Grossman (2007) is a good measure of the behavior of individuals to take risks in the learning process, which opens up the possibility of applying techniques experimental these contexts.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2011
Keywords: Economía; Experimentos; Diseño; Especificaciones; Perspectiva; Economy; Experiments; Design; Specifications; Perspective